Ameliorating effects of L-carnitine and synbiotic co-supplementation on anthropometric measures and cardiometabolic traits in women with obesity: a randomized controlled clinical trial - Fallah, Farnoush; Mahdavi, Reza (Frontiers in Endocrinology, 2023)
Background: Obesity, a multifactorial disorder with pandemic dimensions, is conceded a major culprit of morbidity and mortality worldwide, necessitating efficient therapeutic strategies. Nutraceuticals and functional-foods, are considered promising adjuvant/complementary approaches for weight-management in individuals with obesity who have low adherence to conventional treatments. Current literature supports weight-reducing efficacy of pro/pre/synbiotics or L-carnitine, however, the superiority of nutraceuticals joint-supplementation approach over common single-therapies to counter obesity and accompanying comorbidities, is well documented. This study was designed to assess the effects of L-carnitine single-therapy comparing to L-carnitine and multi-strain/multi-species synbiotic co-supplementation, on anthropometric and cardiometabolic indicators in women with obesity. Methods: The current placebo-controlled double-blind randomized clinical trial was performed on 46 women with obesity, randomly allocated to either concomitant-supplementation (L-carnitine-Tartrate (2500 mg/day) + multi-strain/multi-species synbiotic (1capsule/day)) or mono-therapy (L-carnitine-Tartrate (2500 mg/day) + maltodextrin (1capsule/day)) groups for eight weeks. Participants in both groups received healthy-eating dietary advices. Results: Anthropometric, lipid, and glycemic indices significantly improved in both intervention groups, however, L-carnitine+synbiotic co-administration, elicited a greater reduction in the anthropometric measures including body mass index (BMI), body-weight, neck, waist, and hip-circumferences (p < 0.001, < 0.001, < 0.001, = 0.012, = 0.030, respectively) after adjusting for probable confounders. Moreover, L-carnitine+synbiotic joint-supplementation resulted in a greater reduction in fasting blood sugar (FBS), insulin (though marginal), homeostatic-model-assessment of insulin-resistance (HOMA-IR), and more increment in quantitative-insulin-sensitivity-check-index (QUICKI (p = 0.014, 0.051, 0.024, and 0.019, respectively) comparing to the L-carnitine+placebo mono-supplementation. No significant inter-group changes were found for the lipid profile biomarkers, except for a greater increase in high-density-lipoprotein-cholesterol concentrations (HDL-C) in the L-carnitine+synbiotic group (p = 0.009). Conclusion: L-carnitine+synbiotic co-supplementation was more beneficial to ameliorate anthropometric indices as well as some cardiometabolic parameters comparing to L-carnitine single-therapy, suggesting it as a promising adjuvant approach to ameliorate obesity or associated metabolic complications through potential synergistic or complementary mechanisms. Further longer duration clinical trials in a three-groups design are demanded to verify the complementary or synergistic mechanisms. Clinical Trial Registration: www.irct.ir, Iranian Registry of Clinical Trials IRCT20080904001197N13.